Pyteomics—a Python Framework for Exploratory Data Analysis and Rapid Software Prototyping in Proteomics - Goloborodko, Anton A.; Levitsky, Lev I.; Ivanov, Mark V.; Gorshkov, Mikhail V. (Journal of the American Society for Mass Spectrometry, 2013)
Pyteomics is a cross-platform, open-source Python library providing a rich set of tools for MS-based proteomics. It provides modules for reading LC-MS/MS data, search engine output, protein sequence databases, theoretical prediction of retention times, electrochemical properties of polypeptides, mass and m/z calculations, and sequence parsing. Pyteomics is available under Apache license; release versions are available at the Python Package Index http://pypi.python.org/pyteomics , the source code repository at http://hg.theorchromo.ru/pyteomics , documentation at http://packages.python.org/pyteomics . Pyteomics.biolccc documentation is available at http://packages.python.org/pyteomics.biolccc/ . Questions on installation and usage can be addressed to pyteomics mailing list: pyteomics@googlegroups.com